6(4x-4)=3(8x+3)

Simple and best practice solution for 6(4x-4)=3(8x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(4x-4)=3(8x+3) equation:


Simplifying
6(4x + -4) = 3(8x + 3)

Reorder the terms:
6(-4 + 4x) = 3(8x + 3)
(-4 * 6 + 4x * 6) = 3(8x + 3)
(-24 + 24x) = 3(8x + 3)

Reorder the terms:
-24 + 24x = 3(3 + 8x)
-24 + 24x = (3 * 3 + 8x * 3)
-24 + 24x = (9 + 24x)

Add '-24x' to each side of the equation.
-24 + 24x + -24x = 9 + 24x + -24x

Combine like terms: 24x + -24x = 0
-24 + 0 = 9 + 24x + -24x
-24 = 9 + 24x + -24x

Combine like terms: 24x + -24x = 0
-24 = 9 + 0
-24 = 9

Solving
-24 = 9

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| m=160-15(6) | | [4x-6]=14 | | 3+16r-2=9r+78-4r | | 5(y-2)=-2(12-9y) | | (-x-1)(-6x+4)=2x*3x | | 3+16r-2=94+78-4r | | 3n+9n=96 | | 4.3-2.1t-2.3=7.6 | | .8(18+x)=7 | | 120=255-15w | | 33+15w=5+6x+9 | | .8(1+x)=7 | | 10x-5=2x+43 | | 61+2x=12x-8 | | 6x+17=4x+3 | | 8(18+x)=7 | | 2(x-2)+3=2x+2 | | 2/3=11+4x/5 | | m=255-15(6) | | .18(18+x)=7 | | 2x+5=3x+11 | | 2x*4+7=33 | | 11m-8-6m= | | 4.2q-5.2-5.2q=-2.0q-1.6 | | 3(x-1)=2x+7 | | 3x^2-16x+2=0 | | 3x^3+12x-24=0 | | 0.5(4x*x)=338 | | 7.85-2.1c=20.75 | | 7x^2+8x-4=0 | | y-27=-13 | | -7x^2+8x-4=0 |

Equations solver categories